Pengaruh Layanan Bimbingan Kelompok “Menggunakan Teknik Problem Solving“Terhadap Kesiapan Belajar di Masa Pandemi Pada Siswa Kelas XI IPS 2 SMAN 9 Kota Bengkulu - sari, widya kartika; ariani, winda ade; perdana, meysi (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2023)
This study aims to determine the level of student learning readiness in "pandemic period before (pretest) and after (posttest) group guidance services are given using problemsolving to determine the effect of group guidance services using techniques  solving on student readiness to learn during the pandemic. The method used in this study was an experimental method in the form of a one-"group pretest-posttest. The population in this study was all students of class XI IPS 2 "SMAN 9 Bengkulu City, totaling 26 students. The sample was determined using atechnique random with a total of 12 students in class XI IPS 2. After the data was collected and analyzed using the Wilcoxon test. The research results are as follows: 1. "students before being given group guidance services "using problem solving , there is 1 student with "low categoryein .techniques 2 There is a significant effect of group guidance services using problem solving on learning readiness during the "in class XI IPS 2 SMAN 9 Bengkulu City.